M.V. "Bunga Chempaka" : trim, stability and longitudinal strength calculation - 5105 Osaka Shipbuilding Co. Ltd. Designing Department. Initial Designing Section; Malaysian International Shipping Corporation Berhad (Osaka : [s n], 1972)
19